Astrocytes in neuroendocrine systems: An overview. (20th May 2019) - MacDonald, Alastair J.; Robb, Josephine L.; Morrissey, Nicole A.; Beall, Craig; Ellacott, Kate L. J.
Abstract: A class of glial cell, astrocytes, is highly abundant in the central nervous system (CNS). In addition to maintaining tissue homeostasis, astrocytes regulate neuronal communication and synaptic plasticity. There is an ever‐increasing appreciation that astrocytes are involved in the regulation of physiology and behaviour in normal and pathological states, including within neuroendocrine systems. Indeed, astrocytes are direct targets of hormone action in the CNS, via receptors expressed on their surface, and are also a source of regulatory neuropeptides, neurotransmitters and gliotransmitters. Furthermore, as part of the neurovascular unit, astrocytes can regulate hormone entry into the CNS. This review is intended to provide an overview of how astrocytes are impacted by and contribute to the regulation of a diverse range of neuroendocrine systems: energy homeostasis and metabolism, reproduction, fluid homeostasis, the stress response and circadian rhythms.